Development of Digital-Based Ludo Game Media Material on How We Live and Grow in the Science Subject for Grade V in Elementary Schools - Putrawan, Putu Rendy; Primayana, Kadek Hengki; Pancaria, I Nyoman (Indonesian Journal Publisher, 2025)
This study aims to develop digital-based Ludo game media as a learning media on the material